The critical control of arkosic sandstone porosity on deformation band formation: Insights from the Shulu across-fault borehole in the Bohai Bay Basin, China. (February 2021) - Liu, Zhida; Fu, Xiaofei; Deng, Shang; Meng, Lingdong; Wang, Haixue; Sun, Yonghe; Chen, Zaihe
Abstract: Fewer studies have focused on subsurface deformation bands than deformation bands in outcrops. In this work, we studied the subsurface deformation bands in high-porosity sandstones from the Shulu borehole in the Bohai Bay Basin. The Shulu borehole was drilled through the Xicaogu normal fault with a displacement of 140 m, and the recovered core contains deformation bands and fractures in the damage zones. This study focused on the structural characteristics of subsurface deformation bands with burial depths between 2504.4 m and 2506.2 m. The critical porosity limit of host sandstone for the formation of deformation bands and fractures was determined. The host sandstones in the Shulu borehole are predominantly arkose. The subsurface deformation bands in the Shulu borehole are suggested to be compactional shear bands. We find that the subsurface deformation bands have identical characteristics to those in outcrops, except that they do not show strong positive reliefs. These bands are characterized by protocataclasis and cataclasis and organized into localized and conjugate networks. Compared to the host rocks, the subsurface deformation bands show porosity reductions of 7.7–27.7% and permeability reductions of 1–3 orders of magnitude. Three porosity intervals of the host-rock with different deformation styles can be identified in the Shulu borehole core: 1) host sandstone with porosities greater than 14.3%, which develop deformation bands exclusively; 2) host sandstone with porosities less than 10.8%, which develop fractures; and 3) the transition zone, where the porosities of host sandstone are 10.8–14.3%, and the deformation styles are characterized by both deformation bands and fractures. The critical porosity limit of host rocks in terms of the formation of deformation bands and fractures suggests that porosity is a major factor controlling the formation of fractures and deformation bands. Deformation bands and fractures have counteracting effects on the fluid flow in the transition zone. Highlights: Subsurface deformation bands were investigated from in an across-fault borehole. Compactional shear bands with protocataclasis and cataclasis are defined in the Shulu borehole. Three host-rock porosity intervals with different deformation styles were identified. Deformation bands and fractures could coexist in transition zones with porosities ranging 10.8–14.3%. Deformation bands and fractures have counteracting effects on fluid flow in the transition zone.